2016
DOI: 10.1016/j.ihj.2015.09.032
|View full text |Cite
|
Sign up to set email alerts
|

Role of cardiac MRI in nonischemic cardiomyopathies

Abstract: Cardiac magnetic resonance (CMR) with its higher spatial resolution is considered the gold standard for evaluating ventricular mass, volumes, and ejection fraction. CMR can be used for accurate diagnosis of several conditions, especially cardiomyopathies. The purpose of this article is to review the utility of CMR in the diagnosis and management of nonischemic cardiomyopathies. We have reviewed both common and rare types of nonischemic cardiomyopathies in detail and elaborated on the specific CMR findings in e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 20 publications
0
15
0
6
Order By: Relevance
“…Available long-term follow-up (FU) studies focusing on LVremodeling have usually been based on echocardiography (15,16). However, CMR offers higher spatial resolution and higher inter-study reproducibility and has thus become the gold standard for LV-volume quantification (17)(18)(19)(20). Feature-tracking techniques enable the assessment of myocardial deformation imaging as strain.…”
Section: Introductionmentioning
confidence: 99%
“…Available long-term follow-up (FU) studies focusing on LVremodeling have usually been based on echocardiography (15,16). However, CMR offers higher spatial resolution and higher inter-study reproducibility and has thus become the gold standard for LV-volume quantification (17)(18)(19)(20). Feature-tracking techniques enable the assessment of myocardial deformation imaging as strain.…”
Section: Introductionmentioning
confidence: 99%
“…Myocarditis is an inflammation of the myocardium that can be caused by a variety of etiologies, commonly viral, but also toxins, drugs, and autoimmune processes (1). The usual patterns of clinical presentation include chest pain, arrhythmias, and heart failure.…”
mentioning
confidence: 99%
“…A meta-analysis of four studies performed on 1063 patients, followed for an average of 3.1 years, demonstrated that the presence of LGE had an odds ratio of 5.7 for heart failure death, 2.9 for cardiac death and 4.5 for all-cause mortality [51].…”
Section: Cmr As a Tool For Establishing The Etiology Of Cardiomyopathiesmentioning
confidence: 99%